Ministry of Finance Decree No. 204 Of The Year 2013 On Amending Some Provisions of the Executive Regulations of the Customs Law = وزارة المالية قرار رقم 204 لسنة 2013 بتعديل بعض أحكام اللائحة التنفيذية لقانون الجمارك - The Middle East Library for Economic Services (The Middle East Library for Economic Servicesر, 2025)
English & Arabic.